The role of flavonoids in digestive tract cancer prevention - a review article - Niemiec, Rafał; Branewska, Justyna; Ostrowska, Barbara; Matysek, Mikołaj; Olszanicka, Anna; Imioło, Jan; Maciąg, Anna; Hop, Izabela; Kołodziejczyk, Kacper; Galas, Adam (Journal of Education, Health and Sport, 2023)
Introduction: Flavonoids are bioactive chemical compounds crucial for the functioning of plant organisms. Recently, they have been intensively studied in search of their potential application in medicine. One of the most popular fields in that regard is oncology. Digestive tract cancers are still a challenge for contemporary medicine. Our diet seems to have a direct impact on the etiology of colorectal, gastric, and esophageal cancers. The relationship between the consumption of flavonoids, their specific fractions, and digestive tract cancer morbidity is nowadays frequently investigated. Purpose: This review article aims to discuss the most recent scientific reports and summarize the current state of knowledge, considering the role of flavonoids in digestive tract cancer prevention. Materials and methods: Our work is based on articles accessed through medical information databases (Google Scholar, PubMed, CrossRef), various scientific books, and official NFZ and WHO-certified sites. Results: Total flavonoid intake lowers gastric and esophageal cancer morbidity. A high amount of dietary catechins prevents the growth of gastric and colorectal cancer. Increased consumption of anthocyanidins, flavones, and flavanones decreases esophageal cancer morbidity. Isoflavones, procyanidines, anthocyanidins, flaonols, and flavones severely decrease the chance of developing colorectal cancer. Conclusions: Flavonoids can play an important role in digestive tract cancer prevention. They suppress the growth of colorectal, gastric, and esophageal cancers. Nevertheless, new, high-quality studies are needed in order to compile adequate procedures and bring new, potential drugs to the market.